Development of a sample preparation method for acrylamide determination in cocoa via silylation. Issue 29 (14th July 2016) - Surma, Magdalena; Sadowska-Rociek, Anna; Cieślik, Ewa
Abstract : This paper reports the development of a rapid and simple sample preparation method for acrylamide (AA) determination in cocoa powder through conversion to N, O -bis(trimethylsilyl)acrylamide. Abstract : This paper reports the development of a rapid and simple sample preparation method for acrylamide (AA) determination in cocoa powder through conversion to N, O -bis(trimethylsilyl)acrylamide. The AA level was quantified in relation to an acrylamide-d3 internal standard using gas chromatography coupled with ion-trap mass spectrometry in the single ion monitoring mode (GC-SIM-MS). The analytical procedure consisted of extraction with an organic solvent (acetonitrile with/without hexane addition), extract purification by dispersive solid-phase extraction (d-SPE) using various sorbents (SAX, C18, ENV, Florisil) apart from the PSA sorbent, followed by derivatisation with N, O -bis (trimethylsilyl) trifluoroacetamide (BSTFA) and finally chromatographic analysis (GC-SIM-MS) using a deuterated internal standard. Nine variants of the method were tested. The usefulness of the method has been verified based on the recovery ratio of acrylamide. The obtained results showed that the best recovery of 98.2% with RSD lower than 10% was obtained using a combination of sorbents PSA and C18 with the addition of hexane in the initial stage of the extraction. The developed method has been successfully applied to the determination of acrylamide in 9 cocoa powder and 30 chocolate (dark, milk and white) samples purchased at a Polish supermarket. The results of AA content ranged from 54.2 to 168.0 μg kg −1 and from 25.5 to 256.1 μg kg −1 in cocoa powder and chocolate, respectively. The obtained results were in good agreement with literature reports.